Pengaruh Financial Distress, Intensitas Modal dan Risiko Litigasi terhadap Konservatisme Akuntansi: Studi pada Perusahaan Sektor Perbankan Yang Terdaftar Bursa Efek Indonesia Tahun 2018-2022 - Nezari, Tata; Serly, Vanica (Jurnal Eksplorasi Akuntansi, 2025)
The purpose of this research is to examine the influence of financial distress, capital intensity and litigation risk on accounting conservatism. The sample in this research is banking sector companies listed on the Indonesia Stock Exchange in 2018-2022. sampling was carried out using purposive sampling technique. The total sample used was 32 companies with a total of 161 sample observations. This study used descriptive analysis. Based on the results of statistical tests, financial distress and capital intensity have no effect on accounting conservatism, while litigation risk has a positive effect on accounting conservatism.